INTELLECTUAL CAPITAL ANALYSIS USING THE M-VAIC METHOD ON STOCK PRICES THROUGH PROFITABILITY IN COMPANIES IN THE IDXTECHNO INDEX ON THE INDONESIAN STOCK EXCHANGE - Safira; Nisrul Irawati; Fahmi Natigor Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to determine the influence of Intellectual Capital using the modified value added intellectual coefficient (M-VAIC) method on share prices through profitability in companies on the IDXTECHNO index on the Indonesia Stock Exchange. The research carried out was quantitative research in the form of descriptive verification methods and the type of data used was quantitative data. The population of this study consists of 42 companies listed on the IDXTECHNO index on the IDX for the 2017-2022 period. The sample for this research consisted of 8 companies based on the criteria set by the researchers. The data analysis method uses PLS (Partial Least Square) which is structural equation analysis (SEM) via SmartPLS software. The results of this research show that Intellectual capital is partially proven to have a positive and significant influence on share prices and profitability. Meanwhile, profitability is proven to have no significant influence on share prices. The next results prove that profitability is unable to mediate the influence of intellectual capital on share prices.